THE INFLUENCE OF PUBLIC RELATIONS CAMPAIGNS ON HOUSEWIVES' KNOWLEDGE LEVELS REGARDING ENVIRONMENTAL AWARENESS IN EAST JAKARTA - Nisa, Syarifatun; Sudibyo, A.G (Transpublika Publisher, 2024)
Public relations play a crucial role in enhancing the public image of organizations or campaign organizers. It is essential for public relations to develop goal-oriented campaigns. PT DANONE has launched the #SapuJagat campaign to address the issue of plastic waste. The lack of environmental awareness, particularly among housewives in Rambutan Village, Ciracas District, Jakarta, remains a significant concern. The region suffers from low environmental awareness due to insufficient knowledge and infrastructure support. A study was conducted among housewives in RW01 Rambutan Village, Ciracas District, using a quantitative research approach. Respondents were surveyed through a questionnaire to gather data for the research. The study addressed questions on an ordinal scale, covering 26 SPSS questions related to both variables. According to the statistical findings, 10% of housewives were aged 25-30 years, 9% were aged 31-35 years, 9% were aged 36-40 years, 14% were aged 41-45 years, and 9% were aged over 46 years. The research indicates that the Public Relations campaign variable has a positive impact on enhancing the environmental awareness of housewives. Public Relations campaigns have proven to be effective in increasing the knowledge of housewives regarding environmental issues.